1978
DOI: 10.1002/j.1537-2197.1978.tb06141.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracheid Length as an Ecotypic Character in Acer Negundo L.

Abstract: Laboratory germinated seedlings of Acer negundo grown under controlled environmental conditions showed patterns of decreasing cell length (tracheids) with decrease in length of growing season of parental tree's habitat. Populations tested represented a range in latitude of 15 degrees (Texas to Canada) and the results indicate populational response to shorter growing seasons being reflected in xylem development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Besides Acacia melanoxylon (Wilkins and Papassotiriou, 1989), four Rhododendron species , and Alnus nepalensis (Noshiro et al, 1994) mentioned earlier, Liquidamber styraciflua is known to have latitudinal trends in length of fibers, which lengthen in southern latitudes (Hunter and Goggans, 1969). Winstead (1978) further showed that similar ecotypic differentiation occurs also in Acer negundo from Quebec, Canada, to Texas, USA, resulting in longer fibers in southern latitudes. They showed that seedlings from southern latitudes (in the Northern Hemisphere) always have longer fibers irrespective of growth conditions and concluded that ecotypic differentiation in this species, not acclimatization, causes latitudinal variation in fiber length.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Besides Acacia melanoxylon (Wilkins and Papassotiriou, 1989), four Rhododendron species , and Alnus nepalensis (Noshiro et al, 1994) mentioned earlier, Liquidamber styraciflua is known to have latitudinal trends in length of fibers, which lengthen in southern latitudes (Hunter and Goggans, 1969). Winstead (1978) further showed that similar ecotypic differentiation occurs also in Acer negundo from Quebec, Canada, to Texas, USA, resulting in longer fibers in southern latitudes. They showed that seedlings from southern latitudes (in the Northern Hemisphere) always have longer fibers irrespective of growth conditions and concluded that ecotypic differentiation in this species, not acclimatization, causes latitudinal variation in fiber length.…”
Section: Discussionmentioning
confidence: 75%
“…They showed that seedlings from southern latitudes (in the Northern Hemisphere) always have longer fibers irrespective of growth conditions and concluded that ecotypic differentiation in this species, not acclimatization, causes latitudinal variation in fiber length. Winstead (1978) further showed that similar ecotypic differentiation occurs also in Acer negundo from Quebec, Canada, to Texas, USA, resulting in longer fibers in southern latitudes. Although correlation with other anatomical features of wood are not clarified, these studies indicate that significant latitudinal trends exist in the wood anatomy of some species backed by genotypical diversification.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, it provides another source ofevidence for the evolutionary evaluation of the adaptive radiation of species into different ecological habitats (e.g., Carlquist, 1969Carlquist, , 1970Carlquist, , 1980Baas, 1973;Winstead, 1978). Wood anatomy in particular has shown to be useful in the assessment of systemic relationships among and within genera and families.…”
mentioning
confidence: 99%
“…Wood anatomy in particular has shown to be useful in the assessment of systemic relationships among and within genera and families. Furthermore, it provides another source ofevidence for the evolutionary evaluation of the adaptive radiation of species into different ecological habitats (e.g., Carlquist, 1969Carlquist, , 1970Carlquist, , 1980Baas, 1973;Winstead, 1978). Several recent studies have demonstrated that the anatomical features of wood provide strong correlates of water flow and hydraulic conductance in relation to habitat adaptation (Dimond, 1966;Bissing, 1982;Gibson, Calkin, and Nobel, 1984).…”
mentioning
confidence: 99%